Catheter-Directed Thrombolysis in the treatment of acute Portomesenteric Vein Thrombosis after Laparoscopic Sleeve Gastrectomy - Ali Barah (14777533) (2022)
Background Portomesenteric Vein Thrombosis (PMVT) following Laparoscopic Sleeve Gastrectomy (LSG) is an uncommon but potentially debilitating complication. Catheter-Directed Thrombolysis (CDT) has an evolving role in recanalizing the venous flow and preventing thrombus propagation. Therefore, it can be used as an alternative or in combination with systemic anticoagulants in selected patients. We report two trans-hepatic and trans-splenic CDT. The patient’s clinical details, radiological findings, safety, and efficacy are reported. Cases presentation Two patients presented to the Emergency Department (ED) within 14 days of surgery. The presenting complaints were generally nonspecific. The diagnosis of PMVT was established in both patients based on abdominal Contrast-Enhanced Computed Tomography (CECT). The two patients received a combined therapy of subcutaneous (SC) heparinization and CDT using a trans-hepatic approach in case 1 and a trans-splenic approach in case 2. Subsequent post-procedure venograms and CECT were performed and showed significant thrombus resolution. Both patients received oral anticoagulant therapy upon discharge with a successful overall recovery. Conclusion PMVT is an infrequent and severe post LSG complication. Various approaches for re-establishing the portal venous flow have been described according to the severity of venous thrombosis. This article describes CDT therapy as a safe and effective option for treating PMVT in symptomatic patients. Other Information Published in: Thrombosis Journal License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12959-022-00415-w